PHYTOCHEMICAL ANALYSIS AND ANTIMICROBIAL ACTIVITY OF POLYALTHIA LONGIFOLIA - M. THENMOZHI; RAJESHWARI SIVARAJ (International Journal of Pharma and Bio Sciences, 2010)
Polyalthia longifolia is a lofty evergreen plant, native to India, commonly planted due to its effectiveness in alleviating noise pollution. The has been used in the traditional system of medicine for the treatment of fever, skin diseases, diabetics and hypertension. A number of biologically active compounds have been isolated from the plant. However, its antimicrobial activity has not been investigated still now. Hence it was considered to evaluate the premilinary phytochemical analysis and antimicrobial activity. The premillinary phytochemical analysis and antimicrobial activity of different extarcts (petroleum ether, chloroform, ethyl acetate, ethanol and aqueous) of leaves of Polyalthia longifolia was studied against six different bacteria by disc diffusion method. The various metabolites present in all the extracts. Among various solvent extracts studied, chloroform extract showed higher degree of inhibition followed by ethylacetate, ethanol, petroleum ether and aqueous.